Performance Evaluation of a Modified RPL Routing Protocol Enabling Detection of Version Number and Rank Decrease Attacks in 6LoWPAN-based Wireless Sensor Networks - Przemyslaw MACIEJKO; Jaroslaw KRYGIER (Communications of International Proceedings, 2025)
This paper presents mechanisms for detecting Version Number and Rank Decrease Attacks on a sensor network based on IEEE 802.15.4/6LoWPAN technology with the RPL routing protocol. In addition to detecting intruders carrying out the indicated attacks, the presented mechanisms also minimize the attack's effects. The tests of the developed solutions indicate high intruder detection efficiency, even with a significant number of simultaneously attacking nodes. Furthermore, using the developed mechanisms significantly reduces the energy consumption of network nodes during an attack, and minimizes signaling traffic.
Keywords: WSN; RPL; Version Number Attack; Rank Decrease Attack